Sam: Schelguigius Silesius S. Th. Doct: et Prof: Publ: Athen Gedan. Rect: et ad S.S. Trinit. Past. / F. C. Göbel. - Göbel, Friedrich Carl (16..-17..) (1715)
Przedstawia portret siedzący na tle biblioteki Samuel Schelwig (1643-1715).